2002
DOI: 10.1128/jvi.76.15.7506-7517.2002
|View full text |Cite
|
Sign up to set email alerts
|

Robust Recall and Long-Term Memory T-Cell Responses Induced by Prime-Boost Regimens with Heterologous Live Viral Vectors Expressing Human Immunodeficiency Virus Type 1 Gag and Env Proteins

Abstract: We investigated long-term memory and recall cellular immune responses to human immunodeficiency virus type 1 (HIV-1) Env and Gag proteins elicited by recombinant vesicular stomatitis viruses (VSVs) expressing Env and Gag. More than 7 months after a single vaccination with VSV-Env, ϳ6% of CD8 ؉ splenocytes stained with major histocompatibility complex class I tetramers containing the Env p18-I10 immunodominant peptide and showed a memory phenotype (CD44 Hi ). The level of tetramer-positive cells in memory was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 52 publications
1
55
0
Order By: Relevance
“…In inbred mice, priming with VSV Gag and boosting with vaccinia virus Gag generated about five times more recall and long-term CD8 ϩ T cells than a VSV Gag prime and VSV Gag (G-exchange) boost (11). In macaques a clear trend in the same direction is evident, but the differences in the immune responses do not reach statistical significance.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In inbred mice, priming with VSV Gag and boosting with vaccinia virus Gag generated about five times more recall and long-term CD8 ϩ T cells than a VSV Gag prime and VSV Gag (G-exchange) boost (11). In macaques a clear trend in the same direction is evident, but the differences in the immune responses do not reach statistical significance.…”
Section: Discussionsupporting
confidence: 52%
“…These studies showed that mice immunized with an rVSV expressing HIV-1 Gag and boosted with a completely heterologous vaccinia virus recombinant expressing HIV-1 Gag generated a fivefold increase in peak Gag-specific CD8 ϩ T cells relative to the levels seen in mice immunized with a VSV vector and boosted with a VSV G protein exchange vector expressing Gag (11). The population of Gag-specific T cells persisting long term was also increased fivefold by the heterologous vaccinia boost.…”
mentioning
confidence: 83%
“…We found that vaccination with STxB-OVA induced OVA-specific CD8 + T cells detected ex vivo without the need for in vitro restimulation, and this response was long-lasting, as it was still observed at least 3 months after immunization. Such robust and long-lasting memory CD8 + T cell responses have been observed with recombinant viruses [57,58] and ex vivo DC pulsed with antigens [59,60] but with very few carrier proteins [61,62].…”
Section: Discussionmentioning
confidence: 85%
“…infection. 23,25 In this study, the results of CTL activity demonstrated that immunization with vaccine in combination with NLX and alum mixture did not show any significant difference vs. the alum adjuvanted group. However, the study of Molla Hassan et al showed that NLX significantly increased CTL activity for a cancer vaccine in comparison to the un-adjuvanted vaccine.…”
mentioning
confidence: 85%